Application of Biourin and Mycorrhizal Fertilizers on the Dynamics of Available P, P Uptake, and Shallot (Allium ascalonicum L.) Yield in Vertisols - Rupa Matheus; Donatus Kantur (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
The aim of this study was to evaluate the effect of application of biourin fertilizer and Mycorrhizal Vesicles Arbuscula (MVA) dosage on P dynamics, P uptake and yield of shallots in vertisols. This study was designed with a factorial design pattern on the basis of a randomized block design (RBD). The treatment tested was the concentration of  biourin (B), with four levels: B10: Concentration of 10 ml.l-1 water, B20: Concentration of 20 ml.l-1 water, B30: Concentration of 30 ml.l-1 of water and B40: Concentration 40 ml.l-1 of water. The second treatment was MVA dose with four levels, namely: M0: Without MVA, M10:10 g.plant-1, M20: 20 g.plant-1 and M30: 30 g.plant-1.  The results showed that the biourin concentration of 40 ml.l-1 of water and the MVA dose of 30 g.plant-1 significantly affected the dynamics of available P in Vertisol. The application of biourin at a concentration of 30 ml.l-1 water showed a P absorption of 15.07% and increased shallot yields by 41.07%. The best application of MVA biofertilizer in vertisols was achieved at a dose of 30 g.plant-1, able to increase plant nutrient P uptake by 152% and increase shallot yield by 72.38% from without MVA.Keywords: Concentration of biourin; MVA dose; P dynamics, Shallot yield